COVID-19 respiratory support in the emergency department setting (2020)
Introduction Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2), which causes the coronavirus disease 2019 (COVID-19), may result in severe complications, multiorgan dysfunction, acute respiratory failure, and death. SARS-CoV-2 is highly contagious and places healthcare workers at significant risk, especially during aerosol-generating procedures, including airway management. Objective This narrative review outlines the underlying respiratory pathophysiology of patients with COVID19 and discusses approaches to airway management in the emergency department (ED) based on current literature. Discussion Patients presenting with SARS-CoV-2 infection are at high risk for acute respiratory failure requiring airway management. Among hospitalized patients, 10-20% require intensive care unit admission, and 3-10% require intubation and mechanical ventilation. While providing respiratory support for these patients, proper infection control measures, including adherence to personal protective equipment policies, are necessary to prevent nosocomial transmission to healthcare workers. A structured approach to respiratory failure in these patients includes the use of exogenous oxygen via nasal cannula or non-rebreather, as well as titrated high-flow nasal cannula and noninvasive ventilation. This review offers several guiding principles and resources designed to be adapted in conjunction with local workplace policies for patients requiring endotracheal intubation. Conclusions While the fundamental principles of acute respiratory failure management are similar between COVID-19 and non-COVID-19 patients, there are some notable differences, including a focus on provider safety. This review provides an approach to airway management and respiratory support in the patient with COVID-19.